ESTIMATING THE EFFECT OF URBAN GROWTH ON CURVE NUMBER USING GIS IN THE ERBIL SUB-BASIN OF THE KURDISTAN REGION OF IRAQ - Ibrahim, Arkan H.; Zaid, Pshtiwan Othman; Abo, Abdulla Abdulwahid (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2026)
The urban development of areas directly affects hydrological processes by changing patterns of surface runoff. Cities growing experience increased flood risks as natural water absorption is reduced by changing permeable ground with structures non-absorbent. The research analyzes how expansion of urban between 2017 and 2023 influenced the Curve Number (CN) in the Erbil Sub-Basin, 1318 km2 using (GIS). This study stands differ from earlier research by focusing solely on how LULC changes affect CN values without considering precipitation data. The study achieves a more precise understanding of urbanization impacts on hydrological responses through its precipitation-independent methodology. This research methodology utilizes high-resolution satellite imagery along with soil classification maps and digital elevation models (DEMs) to determine transformations in land use and land cover (LULC). This study uses the Soil Conservation Service Curve Number (SCS-CN) method to analyze runoff changes caused by urban development. CN values steadily grew from 80.53 in 2017 to 81.50 in 2023 as agricultural and barren lands transformed into urbanized spaces. The growing trend points to an increased risk of urban flooding while decreasing groundwater recharge which makes it essential to develop sustainable water management practices.